Determinan Ketepatan Waktu Pelaporan Keuangan Tahunan Dengan Profitabilitas Sebagai Moderasi - Putri Aprilliani; Happy Sista Devy (Universitas Sumatera Selatan, 2024)
The aim of this research is to examine financial distress, company size and ownership structure on the timeliness of financial reporting with profitability as a moderating variable. This research uses a quantitative descriptive approach. The research population was carried out on industrial and chemical sub-sector companies that were listed on the Indonesia Stock Exchange in 2018-2022. The sampling method used was purposive sampling and a sample of 7 companies was obtained. This research uses descriptive statistical analysis and moderated regression analysis to analyze the data. The results of this research indicate that financial reporting, company size and company ownership structure do not influence the timeliness . In this research, profitability is able to moderate financial distress, company size and ownership structure on the timeliness of financial reporting. This research can provide information regarding factors that influence the accuracy of financial reports so that companies carry out financial reporting in a timely manner.